MODEL PEMBELAJARAN TEMATIK DI MADRASAH IBTIDAIYAH - Buri Buri (Nurul Jadid University, 2019)
Integrative thematic learning is a learning approach that integrates various competencies from various subjects into a particular theme. Integrative thematic learning has one theme that is actually close to the world of students and exists in everyday life. This theme is a unifying material that varies from several subjects. Integrative thematic learning needs to select material from several subjects that may be interrelated. The assessment techniques carried out by the teacher in this learning are in the form of oral tests, written tests, assignments and performance tests. Report cards with integrative thematic learning do not use numbers as ratings but with sentence descriptions and assess all aspects.